PERFORMANCE IMPACT OF DISPATCHING AND ROUTING IN AN AUTOMATED GUIDED VEHICLE SYSTEM - Bang, Inhye; Kim, Byung-In; Kim, Yonggu (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
Dispatching and routing are fundamental operational decisions in automated material-handling systems. Numerous studies have been conducted on these two operational decisions, with more focus being recently made on intelligent routing decisions. However, comparative studies between the effects of dispatching and routing methods have not been reported so far. In this study, we have investigated three dispatching and three routing algorithms and measured their impacts using a simulation model for an automated guided vehicle (AGV) system designed for a real-world production line, in which a grid-type material flow layout is used, and the AGVs need to stop before changing their direction of movement. Two routing algorithms are developed in this study. Simulation experiments revealed that both dispatching and routing algorithms affect the performance of the AGV system, although dispatching methods showed a more significant impact. Good dispatching and routing algorithms are mandatory to improve the overall performance of AGV systems.